Pengaruh Interpretasi Personal dan Interpretasi Non-Personal Terhadap Kepuasan Pengunjung di Museum Pendidikan Nasional - Ilmiati Tsaniah; M. Liga Suryadana; Sutanto Leo (Tourism Scientific Journal, 2022)
This study aims to determine whether the influence of personal interpretation (X1) consist of 4 dimensions, enjoyment, relevant, organized, and thematic and non-personal interpretation (X2) consist of 6 dimensions, sign, interpretation board, map, brochure, audio and audio visual media and interpretative exhibit on visitor satisfaction consisting of revisiting, transaction between product lines, comparison to other and visitors’s immunity to offers by competition. This study uses descriptive and verification testing and the method used is path analysis with the results of a descriptive study of the description of personal interpretations, non-personal interpretations and visitor satisfaction each having average value of 3,50, 3,51, and 3,56  which is on the continuum line in either category. The results of the calculation of the coefficient of determination show that the influence of personal interpretation variables and non-personal interpretations on visitor satisfaction is 50.1%, while the remaining 49.9% is the contribution of other variables not included in the study. The results of the verification analysis are simultaneous and partial testing of the hypotheses simultaneously and partially, simultaneously based on the calculated F value of 197,154 > F table of 3.04 which means it has a significant effect, while partially using the t test for mama X1 variable has a t value of 4,93 > t table 1,962 and X2 of 11,98 > t table 1,962 can be interpreted that there is a significant influence between each independent variable on the dependent variable.